2013
DOI: 10.5812/ircmj.6418
|View full text |Cite
|
Sign up to set email alerts
|

Extensive cerebral Sinovenous Thrombosis in a 5 Year Old Girl, Following Mild Dehydration. (Case Report and Review of Literature)

Abstract: Cerebral sinovenous thrombosis (CSVT) in children has rarely been reported in the literature, especially without underlying disorder. It has increasingly been diagnosed due to clinical awareness and sensitive neuroimaging techniques. The aim of this article was to report a case of cerebral sinovenous thrombosis without underlying disorder. We reported a 5 year old girl, presented with severe headache and seizure. She had a history of fever and diarrhea before the onset of headache. Neuroimaging showed evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…In our database, 1 death was noted. Previously, the data suggested that a long follow-up should be done for children with CVST since 10% to 20% of them will experience recurrent events [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our database, 1 death was noted. Previously, the data suggested that a long follow-up should be done for children with CVST since 10% to 20% of them will experience recurrent events [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, rarely reported infections as the underlying causes of PTC included measles, varicella, Lyme disease, human immunodeficiency virus (HIV), and tuberculosis (16)(17)(18)(19)(20)(21). However, brucellosis has been more commonly reported recently as the trigger for PTC, compared with other mentioned infections (6,(22)(23)(24)(25)(26). As aforementioned, neuroimaging usually offers normal findings in PTC.…”
Section: Discussionmentioning
confidence: 99%